2022
DOI: 10.4094/chnr.2022.28.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a hybrid online and offline program for facilitating father-infant interactions in South Korea: a quasi-experimental study

Abstract: Purpose: This study examined the effects of an educational program for fathers on improving father-infant interactions, child-rearing knowledge, and attachment.Methods: In this quasi-experimental study, the participants were recruited by convenience sampling among fathers with infants (2-6 months of age) residing in three districts of Seoul. Fifteen participants in the experimental group and 17 participants in the control group completed the follow-up investigation. A 5-week online and offline intervention pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Other digital technologies that were used included SMS text messages (7/29, 24%), mobile apps (7/29, 24%), digital videos (5/29, 17%), email (4/29, 14%), videoconferencing (4/29, 14%), and social media (1/29, 3%). Notably, the 14% (4/29) of interventions using videoconferencing modalities were recent, with publication dates of 2021 and 2022 [ 87 , 102 , 103 , 105 ]. Some interventions (11/29, 38%) included more than one type of eHealth component, such as the use of websites and email communication (3/29, 10%), SMS text messages, website resources and modules (2/29, 7%), or a mobile app and website links (2/29, 7%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other digital technologies that were used included SMS text messages (7/29, 24%), mobile apps (7/29, 24%), digital videos (5/29, 17%), email (4/29, 14%), videoconferencing (4/29, 14%), and social media (1/29, 3%). Notably, the 14% (4/29) of interventions using videoconferencing modalities were recent, with publication dates of 2021 and 2022 [ 87 , 102 , 103 , 105 ]. Some interventions (11/29, 38%) included more than one type of eHealth component, such as the use of websites and email communication (3/29, 10%), SMS text messages, website resources and modules (2/29, 7%), or a mobile app and website links (2/29, 7%).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 studies primarily examining efficacy outcomes (ie, how effective the intervention was across various outcomes), 13 (72%) reported a statistically significant intervention effect. Statistically significant intervention effects were reported for father-child attachment and interaction [ 99 , 101 , 102 ]; knowledge about and attitudes toward participation in perinatal care [ 70 ]; smoking cessation and mothers’ secondhand smoking exposure [ 96 ]; parenting self-efficacy and satisfaction [ 72 , 74 , 104 ]; breastfeeding self-efficacy, knowledge, and infant feeding attitudes [ 89 , 92 ]; parental depression and child sadness [ 75 ]; and parental anxiety, depression, and quality of life [ 98 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included parent outcomes were from validated self-report questionnaires. At the relational level, of the 6 studies that reported on parent-child interaction, three used parent-reported questionnaires (Breitenstein et al, 2021;Ehrensaft et al, 2016;Na & Chia, 2008); two used observational data (Baggett et al, 2010;Park & Bang, 2022); and one study used parent-reported and observational (Mogil et al, 2022).…”
Section: Study Characteristicsmentioning
confidence: 99%